2016
DOI: 10.1038/bmt.2016.281
|View full text |Cite
|
Sign up to set email alerts
|

Haploidentical transplantation for pediatric patients with acquired severe aplastic anemia

Abstract: Techniques for haploidentical hematopoietic stem cell transplantation (haplo-HSCT) to treat severe aplastic anemia (SAA) have recently improved, but no protocol has been evaluated in a large number of pediatric patients. Fifty-two children with SAA received haplo-HSCT in our center. The treatment protocol used G-CSF-primed bone marrow with G-CSF-mobilized PBSCs without in vitro T-cell depletion. The conditioning regimen included busulfan/cyclophosphamide and antithymocyte globulin. Fifty-one patients achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
66
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 29 publications
5
66
1
4
Order By: Relevance
“…In addition, recent advances in conditioning regimen, prophylaxis of graft-vs-host disease (GVHD), and supportive care have significantly enhanced therapeutic benefits of HRD-HSCT. More importantly, different centers in China including our center have reported the feasibility and promising outcomes of using HRD-HSCT in patients with acquired SAA, achieving long-term OS of 77.3%-86.1%, [5][6][7][8] which is comparable to outcomes of patients with SAA receiving HLA-identical sibling HSCTs. 8 Furthermore, a recent finding suggests that HRD-HSCT has similar efficacy in the treatment of pediatric SAA compared to IST.…”
mentioning
confidence: 67%
“…In addition, recent advances in conditioning regimen, prophylaxis of graft-vs-host disease (GVHD), and supportive care have significantly enhanced therapeutic benefits of HRD-HSCT. More importantly, different centers in China including our center have reported the feasibility and promising outcomes of using HRD-HSCT in patients with acquired SAA, achieving long-term OS of 77.3%-86.1%, [5][6][7][8] which is comparable to outcomes of patients with SAA receiving HLA-identical sibling HSCTs. 8 Furthermore, a recent finding suggests that HRD-HSCT has similar efficacy in the treatment of pediatric SAA compared to IST.…”
mentioning
confidence: 67%
“…This was reflected in racial distribution of the salvage transplant group in this study as well. Availability of alternate donors with good outcomes in AA is an important area for research and recent studies have shown promising results with haploidentical and combined Haplo‐cord transplants …”
Section: Discussionmentioning
confidence: 99%
“…As these patients tend to be sicker, the number of ICU visits was also significantly higher in this group. Moving toward more upfront trans- 32,33 and combined Haplo-cord transplants. 34,35 There are many limitations to this study that are inherent to administrative database studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bugün EAA için antitimosit globulin (ATG) ve siklosporin-A (CsA) içeren immünosupresif tedaviler (İST) ve hematopoetik kök hücre nakli (HKHN) standart tedaviler olarak kullanılmaktadır. Bu tedaviler sayesinde son dekadlarda AEAA prognozu belirgin şekilde iyileşmiştir (1,4). Özellikle allojenik HKHN çocukluk çağındaki AEAA için devrim niteliğinde bir küratif yaklaşım olmuştur.…”
Section: Introductionunclassified
“…İleri moleküler teknikler, gelişmiş hazırlama rejimleri ve graft versus host hastalığı (GVHH) profilaksi seçenekleri birleştiğinde, eğer insan lökosit antijen (human leucocyte antigen; HLA) tam uyumlu kardeş verici (TUKV) mevcutsa HKHN çocuklardaki edinsel AA için altın standart tedavi olarak kabul edilmektedir (4,5). Farklı ülkelerden gelen veriler, TUKV ile nakil olgularında uzun süreli genel sağ kalımın (GSK) %90'ın üzerinde olduğunu göstermektedir (4). HLA uyumlu aile donörü olmayan çocuklarda ise İST terapö-tik bir seçenek olarak kullanılmaktadır (6).…”
Section: Introductionunclassified